The persistence of reciprocity in international humanitarian law / Bryan Peeler. - Peeler, Bryan, 1969- (Cambridge University Press, 2019)
The expectation of reciprocity continues to be an important factor when states' consider their legal obligations in armed conflicts. In this monograph, Peeler looks at the text and negotiations around the 1949 Geneva Conventions and the Protocols Additional to the Geneva Conventions from 1977 to demonstrate the many places where international humanitarian law maintains expectations of reciprocity. This complements an examination of US policy regarding its Prisoner of War obligations in both the Vietnam War and the Global War on Terror, demonstrating how states make use of the expectation of reciprocity found in international humanitarian law to respond to continued non-compliance by an enemy.